Comparison of the CH and OH Groups as Proton Donors within Hydrogen Bonds - Savannah Rawlings; Steve Scheiner (ChemistryEurope)
The ability of the CH group to act as proton donor is now widely accepted, even if the H bonds (HBs), which it forms are typically much weaker than those of the hydroxyl group, particularly for a sp3‐hybridized C. An NH3 nucleophile is allowed to approach both the terminal methyl group and the hydroxyl of n‐butanol, so as to form either a CH··N or OH··N HB. Density functional theory calculations show that the latter is much stronger than the former. However, the strength of the CH··N HB can be amplified and approach much closer to that of OH··N by appropriate placement of suitable electron‐withdrawing and donating substituents on the butanol. The interaction energy of the CH··N HB reaches above 6–8 kcal mol−1 in several cases, considerably larger than the prototype HB within the water dimer.